2004
DOI: 10.1023/b:sore.0000027410.26010.40
|View full text |Cite
|
Sign up to set email alerts
|

Societal and Managerial Implications of Implicit Social Cognition: Why Milliseconds Matter

Abstract: This article argues for the vulnerability of managerial work to unintended forms of racial and other bias. Recent insights into "implicit social cognition" are summarized, highlighting the prevalence of those mental processes that are relatively unconscious and automatic, and employed in understanding the self and others. Evidence from a response-time measure of implicit bias, the Implicit Association Test, ("IAT";Greenwald, McGhee, and Schwartz, 1998) (Mintzberg, 1973). Implicit bias influences managerial beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 52 publications
0
65
1
2
Order By: Relevance
“…But, System 2 logic should be used for more important decisions, and for decisions with ethical import. Yet, the frantic pace of many of our lives leads us to rely on System 1 thinking, even when System 2 thinking is warranted (Chugh, 2004). Mead et al (2009) found that cognitively busy study participants were more likely to behave unethically than less cognitively busy study participants (for additional empirical support, see Gino et al, 2011).…”
Section: Iii1 Changing Individual Moralitymentioning
confidence: 99%
“…But, System 2 logic should be used for more important decisions, and for decisions with ethical import. Yet, the frantic pace of many of our lives leads us to rely on System 1 thinking, even when System 2 thinking is warranted (Chugh, 2004). Mead et al (2009) found that cognitively busy study participants were more likely to behave unethically than less cognitively busy study participants (for additional empirical support, see Gino et al, 2011).…”
Section: Iii1 Changing Individual Moralitymentioning
confidence: 99%
“…The text of the article suggests that both men and women participated in the study, but there was no breakdown of participants by sex nor was a test for sex differences reported. 4 As Chugh (2004) noted, the second interaction differed significantly from the first interaction: Whereas the first interaction raised no racial issues, the second interaction involved a Black experimenter explicitly asking White participants race-related questions after the participants had completed the race IAT. Chugh incorrectly stated, however, that judges in McConnell and Leibold (2001) were blind to the race of the experimenter; in fact, McConnell and Leibold's procedure section makes clear that judges viewed both the participant and experimenter.…”
mentioning
confidence: 99%
“…Nevertheless, upon visual and auditive perception of these features, everyone is classi ed almost immediately as adept or inept in certain tasks and as free of, or subject to, certain norms, duties and expectations. Everyone including, certainly, employers and employees knows this, if only unwittingly (Chugh 2004). People carry a wealth of social knowledge triggered by the physical cues of their phenotype.…”
Section: Traditional Notions: Ethnic Segregation and Gender Segregationmentioning
confidence: 99%